FLASH: Fluorescently LAbelled Sensitive Hydrogel to monitor bioscaffolds degradation during neocartilage generation. (January 2021) - Onofrillo, Carmine; Duchi, Serena; Francis, Sam; O'Connell, Cathal D.; Caballero Aguilar, Lilith M.; Doyle, Stephanie; Yue, Zhilian; Wallace, Gordon G.; Choong, Peter F.; Di Bella, Claudia
Abstract: Regenerative therapies based on photocrosslinkable hydrogels and stem cells are of growing interest in the field of cartilage repair. Cell-mediated degradation is critical for the successful clinical translation of implanted hydrogels. However, characterising cell-mediated degradation, while simultaneously monitoring the deposition of a distinct new matrix, remains a major challenge. In this study we generated a Fluorescently LAbelled Sensitive Hydrogel (FLASH) to correlate the degradation of a hydrogel bioscaffold with neocartilage formation. Gelatine Methacryloyl (GelMA) was covalently bound to the FITC fluorophore to generate FLASH and bioscaffolds were produced by casting different concentrations of FLASH GelMA, with and without human adipose-derived stem cells (hADSCs) undergoing chondrogenesis. The loss of fluorescence from FLASH bioscaffolds was correlated with changes in mechanical properties, expression of chondrogenic markers and accumulation of a cartilaginous extracellular matrix. The ability of the system to be used as a sensor to monitor bioscaffold degradability during chondrogenesis was evaluated in vitro, in a human ex vivo model of cartilage repair and in a full chondral defect in vivo rabbit model. This study represents a step towards the generation of a high throughput monitoring system to evaluate de novo cartilage formation in tissue engineering therapies. Graphical abstract: Image 1 Highlights: Hydrogel biodegradability is a key parameter for efficient neocartilage generation. FLASH allows a contactless monitoring of hydrogel biodegradability. FLASH is a tool to monitor bioscaffolds during neocartilage generation. FLASH and GAG allow simultaneous assessment of hydrogel biophysical changes.